THE INFLUENCE OF HEDONISM ON THE APPLICATION OF THE DEEP LEARNING MODEL ON THE DEVELOPMENT OF EARLY ADULTHOOD IN STUDENTS - Frezy Paputungan (JCI Publisher, 2026)
Development is a continuous process of qualitative change towards maturity, marked by increased organ function, cognitive, emotional, motoric, and behavioral abilities. Early adulthood is a period of human development from adolescence to adulthood. Early adulthood begins between the ages of 16 and 40. In the human lifespan, adulthood plays an important role as a phase in which individuals experience various changes and adjustments. In this developmental process, several possible behavioral changes are very influential, including hedonism. The view of hedonism is often associated with consumptive and hedonistic behavior. People who adhere to hedonism will always seek ways to obtain pleasure, whether material, physical, or spiritual pleasure. Related to the increasingly advanced world of education, various learning models are implemented as an effort to adapt to the times. One of them is the deep learning learning model, deep learning is a pedagogical approach that focuses on understanding substantial concepts in depth, not just the breadth of material, through meaningful, conscious, and enjoyable (holistic) learning experiences. This study aims to analyze how hedonism in the application of the deep learning learning model influences the development of students' early adulthood, using qualitative descriptive methods. The research results show a significant influence between hedonistic attitudes in the application of deep learning and early adulthood development, as seen through observations and interviews conducted directly during the learning process. One observation revealed that students appeared relaxed and enjoyed group assignments, as some paid to be relieved of responsibility for completing them.